2019
DOI: 10.1002/anie.201902576
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Asymmetric Hydrogenation of N‐Sulfonyl Imines

Abstract: An efficient nickel‐catalyzed asymmetric hydrogenation of N‐tBu‐sulfonyl imines was developed with excellent yields and enantioselectivities using (R,R)‐QuinoxP* as a chiral ligand. The use of a much lower catalyst loading (0.0095 mol %, S/C=10500) represents the highest catalytic activity for the Ni‐catalyzed asymmetric hydrogenations reported so far. Mechanistic studies suggest that a coordination equilibrium exists between the nickel salt and its complex, and that excess nickel salt promotes the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(65 citation statements)
references
References 57 publications
2
61
0
2
Order By: Relevance
“…The existence of Complex‐1 in solution was confirmed by HRMS (see Figure S1 for details). It is very interesting to note that only Complex‐1 was observed, without any Complex‐2 , which differs from that of Ni‐QuinoxP* . The content of Complex‐1 is approximately 50 % when the L/M ratio is 1:1, and it increases to 65 % and 68 % when the L/M ratios are 2:1 or 1:2, respectively (Figure , traces a–d, 25 °C).…”
Section: Figurementioning
confidence: 92%
See 2 more Smart Citations
“…The existence of Complex‐1 in solution was confirmed by HRMS (see Figure S1 for details). It is very interesting to note that only Complex‐1 was observed, without any Complex‐2 , which differs from that of Ni‐QuinoxP* . The content of Complex‐1 is approximately 50 % when the L/M ratio is 1:1, and it increases to 65 % and 68 % when the L/M ratios are 2:1 or 1:2, respectively (Figure , traces a–d, 25 °C).…”
Section: Figurementioning
confidence: 92%
“…Recently, a few examples of Ni‐catalyzed asymmetric hydrogenation of alkenes have been reported by the Chirik and Zhang groups with excellent results . Along with our interest in asymmetric hydrogenation, we have developed the first efficient Ni‐catalyzed asymmetric hydrogenation of imines for the synthesis of chiral amines . It was found that some interactions between the substrate and catalyst improved the catalytic activity, and an appropriate metal/ligand ratio increased the catalyst efficiency.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This journal is © the Partner Organisations 2020 N-sulfonyl imines. 43 Exhibiting one of the highest catalytic activities and an ee of 97% was the complex of the (R,R)-QuinoxP* ligand 27 (Fig. 37) in the reduction of 2-methyl-N-(1phenylethylide-ne)propane-2-sulfonamides.…”
Section: Organic Chemistry Frontiers Reviewmentioning
confidence: 99%
“…Noteworthy developments have been made in recent years in the area of metal-catalyzed hydrogenation of N-bearing heterocyclic compounds, [1] alkenes, [2] and imines [3] to produce pharmaceuticals, petrochemicals, and polymers from natural products on an industrial scale. In this context, researchers have studied many unique homogeneous catalysts based on Mn, [4][5][6] Fe, [7][8][9][10][11] Co, [12][13][14] Ni, [15][16] Rh, [17][18][19][20][21] Ir, [22] Ru, [23,24] and Pd [25,26] with excellent performance. However, owing to the complex multi-step procedures, use of toxic solvents, harsh reaction conditions, and a tedious and cumbersome process of separating the spent catalyst, the currently available methods are not commercially viable.…”
Section: Introductionmentioning
confidence: 99%